Heterogeneity within T Cell Memory: Implications for Transplant Tolerance - Krummey, Scott M.; Ford, Mandy L. (Frontiers in Immunology, 2012)
Adaptive immunity in both mouse and man results in the generation of immunological memory. Memory T cells are both friend and foe to transplant recipients, as they are intimately involved and in many cases absolutely required for the maintenance of protective immunity in the face immunosuppression, yet from the evidence presented herein they clearly constitute a formidable barrier for the successful implementation of tolerance induction strategies in transplantation. This review describes the experimental evidence demonstrating the increased resistance of memory T cells to many distinct tolerance induction strategies, and outlines recent advances in our knowledge of the ways in which alloreactive memory T cells arise in previously untransplanted individuals. Understanding the impact of alloreactive memory T cell specificity, frequency, and quality might allow for better donor selection in order to minimize the donor-reactive memory T cell barrier in an individual transplant recipient, thus allowing stratification of relative risk of alloreactive memory T cell mediated rejection, and conversely increase the likelihood of successful establishment of tolerance. However, further research into the molecular and cellular pathways involved in alloreactive memory T cell-mediated rejection is required in order to design new strategies to overcome the memory T cell barrier, without critically impairing protective immunity.